SIMULATION OF 2-DOF MECHANISM CONTROL SYSTEM FOR SATELLITE COMMUNICATION ANTENNAS - Maja Saputra, Hendri
Two degrees of freedom driving mechanisms (MP 2-DOF) are widely used in various fields, not only civilian but also defense. Especially in the field of defense, the dependence on imported products resulting the leakage of confidential data and the difficulty of repairing and maintenance. Indonesian Institute of Sciences (LIPI) solves that problem through research activities conducted by several research centers, including radar research by the Electronics and Telecommunications Research Center (P2ET), optronics stabilized platform research by the Research Center for Calibration, Instrumentation and Metrology (P2KIM) and moving target locking research by the Research Center of Electric Power and Mechatronics (P2Telimek). The purpose of this research is to develop techniques for controlling a 2-DOF drive system used in satellite communication antennas that support all the LIPI research activities. The scope of this study includes: reviewing IMU sensor algorithms to be applied in the sensor PhidgetSpatial brand 3/3/3, deriving the inverse angle equation to compensate the vehicles movement and derives dynamical equations and its simulation using PID control. The research methodology begins with a literature review, derivation of the attitude and inverse angle equation, modeling the dynamics by two methods (Lagrange method by assuming point masses on the joints and the Newton-Euler method for point masses at the Center of Gravity / COG), and linearize the dynamics model and control simulation using a MP 2-DOF belongs to LIPI. The following results have been obtained. Reading PhidgetSpatial 3/3/3 with Matlab should consider a sampling time less than 32 ms. The most appropriate inverse angle method to compensate for the vehicles movement is "rotation matrix method" with much faster process, where the maximum error of the method to Jacobian matrix is 0.03º for Pan and 0.02º for Tilt. The maximum actuator power required is 1.72 kW for Pan and 2.69 kW for Tilt. In PID control simulation, the constant[kp, ki, kd] obtained for Pan are [70, 0.001, 30] while for the Tilt are [720, 880, 220]. PID control simulation comparison between linear systems and non-linear system visually showed the same response in the steady-state, whereas in the transient region have differences.